2022
DOI: 10.1111/apha.13815
|View full text |Cite
|
Sign up to set email alerts
|

Acute adaptation of renal phosphate transporters in the murine kidney to oral phosphate intake requires multiple signals

Abstract: Aims Dietary inorganic phosphate (Pi) modulates renal Pi reabsorption by regulating the expression of the NaPi‐IIa and NaPi‐IIc Pi transporters. Here, we aimed to clarify the role of several Pi‐regulatory mechanisms including parathyroid hormone (PTH), fibroblast growth factor 23 (FGF23) and inositol hexakisphosphate kinases (IP6‐kinases) in the acute regulation of NaPi‐IIa and NaPi‐IIc. Methods Wildtype (WT) and PTH‐deficient mice (PTH‐KO) with/without inhibition of FGF23 signalling were gavaged with Pi/salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Insulin may also play a role in this response; while this was not measured in the current experimental series, insulin was not found to increase following acute Pi loads in rats and humans 4,6 . Factors associated with FGF23 signaling were also investigated by Daryadel et al and an early response gene associated with FGF23 signaling was found to increase 4 h after Pi loading in both genotypes, in line with an increase in FGF23 levels 3 . Interestingly, FGF23 signaling was increased in Pth ‐deficient mice already after 1 h, before changes in FGF23 levels could be observed.…”
supporting
confidence: 47%
See 4 more Smart Citations
“…Insulin may also play a role in this response; while this was not measured in the current experimental series, insulin was not found to increase following acute Pi loads in rats and humans 4,6 . Factors associated with FGF23 signaling were also investigated by Daryadel et al and an early response gene associated with FGF23 signaling was found to increase 4 h after Pi loading in both genotypes, in line with an increase in FGF23 levels 3 . Interestingly, FGF23 signaling was increased in Pth ‐deficient mice already after 1 h, before changes in FGF23 levels could be observed.…”
supporting
confidence: 47%
“…6 In the current study, Daryadel et al explore the effect of acute Pi loading via gavage in wild-type mice and utilize transgenic mice lacking the Pth gene to define PTHindependent effects in this response. 3 In contrast to the previous experiments in rats, an acute Pi load via gavage in mice leads to substantial initial elevations in plasma Pi similar to that seen with intravenous infusion in rats and both intravenous and duodenal infusions in humans. 4,6 Using a comprehensive approach of functional measurements that include renal excretion of Pi and expression of the Na + / Pi cotransporters in renal brush border membrane isolates as well as relevant hormones and transmitters, Daryadel et al sought to understand in further detail the mechanisms driving the renal defense against Pi overload.…”
Section: Sorting Out the Rapid Renal Response To An Oral Phosphate Loadmentioning
confidence: 61%
See 3 more Smart Citations